Limited Attention and Post-Earnings Announcement Drift: Evidence from China's Stock Market - Qian Chen; Xiang Gao; Gangchen Liu (International Journal of Economics and Financial Issues, 2021)
This paper utilizes Chinese stock data to provide further evidence on the power of limited attention theory in explaining post-earnings announcement drift. As retail investors prevail in China and they are easily distracted by market swings, we should expect severe attention problems, resulting in larger underreaction to firm information and higher sensitivity to market movement, i.e., the so-called “market movement effect”. After accounting for special arrangements such as preannouncements and earnings previews, we confirm a strong presence of this effect in Chinese stock market, given the “Friday effect” and “announcement concentration effect” being controlled for. Moreover, the effect is asymmetric in market up and down, and becomes more pronounced for small-cap and value stocks.